2016
DOI: 10.1080/01639625.2016.1169740
|View full text |Cite
|
Sign up to set email alerts
|

The Dirty Work of Poker: Impression Management and Identity

Abstract: Poker has penetrated mainstream popular culture in recent years with the emergence of internet poker sites and television coverage of poker's largest events. However, images of seedy, back alley poker games and riverboat gamblers persist when someone identifies themselves as a poker player. How do poker players deal with the preconceived notions about who they are and what they do? What are they willing (or have) to do to maintain this identity? How does being a poker player affect their family life and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 37 publications
3
26
0
Order By: Relevance
“…There are both similarities and differences between Hayano's (1977Hayano's ( , 1982 description of the poker world and the descriptions of more recent authors (Bjerg 2010(Bjerg , 2011Bouju, Grall-Bronnec, Quistrebert-Davanne, Hardouin, & Venisse, 2013;Laakasuo, Palomäki, & Salmela, 2016;McCormack & Griffiths, 2012;Palomäki et al, 2013b;Radburn & Horsley, 2011;Recher & Griffiths, 2012;Vines & Linders, 2016;). Hayano's informants preferred Five-Card Draw California style, a game of significantly less open information and skill than the most common poker variants played today.…”
Section: Studies On Poker Learningmentioning
confidence: 94%
See 1 more Smart Citation
“…There are both similarities and differences between Hayano's (1977Hayano's ( , 1982 description of the poker world and the descriptions of more recent authors (Bjerg 2010(Bjerg , 2011Bouju, Grall-Bronnec, Quistrebert-Davanne, Hardouin, & Venisse, 2013;Laakasuo, Palomäki, & Salmela, 2016;McCormack & Griffiths, 2012;Palomäki et al, 2013b;Radburn & Horsley, 2011;Recher & Griffiths, 2012;Vines & Linders, 2016;). Hayano's informants preferred Five-Card Draw California style, a game of significantly less open information and skill than the most common poker variants played today.…”
Section: Studies On Poker Learningmentioning
confidence: 94%
“…There are also possible play formats that are highly unusual in a casino or poker club, such as playing against only one opponent. The importance of professional players playing several tables simultaneously, getting less variance, and attacking several weak players at the same time has been discussed by McCormack and Griffiths ( 2012) and Vines and Linders (2016). In describing card rooms before online poker, Hayano (1982) stated that he usually played with the same players every day and that meeting new and potentially inexperienced players was almost considered hitting a goldmine.…”
Section: What Learning Artefact Was Described As the Most Rewarding?mentioning
confidence: 99%
“…Amateur gamblers peruse opposite alibis for the same reasons: They account for gambling as inconsequential leisure because the gambling stigma of addiction and financial folly far outstrips the mild disapproval stirred by “frivolous fun” ( Smith & Preston, 1984 ). And like professional gamers, professional gamblers neutralize the stigma of gambling by accounting for it as routine, professional, and gainful labor ( Vines & Linders, 2016 ).…”
Section: Strategies Of Embarrassment Deflectionmentioning
confidence: 99%
“…A survey of 179 online poker players (Hopley & Nicki, 2010), a qualitative study of 12 regular offline poker players (Vines & Linders, 2016), and a study of a high earning sub group of 31 online poker players (Hopley, Wagner, & Nicki, 2014) all found that the average player spent more than 30 hours a week on poker. Even though studies have shown that playing poker may be highly time-consuming and therefore affect the player's education (Biolcati et al, 2015;Bjerg, 2010;Griffiths et al, 2010;Hing et al, 2014), little is known about why poker is so time-consuming and how the poker players themselves describe their struggle to combine their studies with gambling.…”
Section: Poker Is Highly Time Consumingmentioning
confidence: 99%
“…This leads to fewer new players coming in to the poker sites and that again makes the games more evenly matched. The importance of playing against inferior players for the professional players is earlier discussed by McCormack & Griffiths (2011) as well as Vines & Linders (2016).…”
Section: What Makes Combining Poker With Education Difficult?mentioning
confidence: 99%